Análise dos determinantes de estrutura de capital das principais empresas do setor de transporte aéreo civil brasileiro - Samú, Gustavo Brito (Universidade Federal de São Carlos, 2021)
There is still no consensus in the financial literature regarding the companies’ capital structure determinants. This discussion has been going on since Durant (1952) proposed the traditional theory - which predicts that there is an ideal configuration of the way companies finance themselves - and was opposed by Modigliani and Miller (1958) - who developed the theory that there is no ideal configuration. Since then, several empirical studies have been developed to test these theses and new ideas have emerged on the subject. However, most of these studies have been carried out in markets quite different from the Brazilian one and, even in these, definitive convictions about the theoretical assumptions of the subject have not yet been defined. This work aims to continue these empirical studies by validating theoretical hypotheses based on data collected from the financial statements of the 3 largest companies in the Brazilian civil air transport sector. For this, using quarterly accounting data extracted from the websites of the companies studied, the statistical technique of multiple linear regression was used, which allowed to evaluate the relationship (positive or negative) between the defined accounting indices and to test the hypotheses raised. The results suggest that the profitability factor is decisive for the companies' capital structure and does not allow us to draw any further conclusions about the others.
Analysis of the capital structure determinants of the main companies in the Brazilian civil air transport sector
Keywords: Determinantes de estrutura de capital; Regressão linear múltipla; Endividamento; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA ECONOMICA::ESTUDO DE MERCADO